Enhancement of the performance of solar chimneys using associated petroleum gas - Nasser Al-Abadi; Amer K. Ahmed; Sameer Algburi; Omer K. Ahmed (International Journal of Sustainable Energy, 2024)
ABSTRACTIn this article, an idea has been presented that utilizes the heat produced from the petroleum gas burning accompanying the process of oil extraction to enhance the solar chimney performance. The simulation software tool ANSYS Fluent 2020R1 was used to know the possibility of exploiting this waste energy of gas and combining it with a solar chimney. Seven gas channel configurations were tested on the solar chimney to determine which can produce the most electricity. The simulation results showed that this idea could be exploited to produce higher electric energy, and the efficiency of the solar chimney was increased so that the electric energy production process continues for 24 hours instead of production during the sunshine period only. Different designs were considered for the channels inside the solar collector. Case1 and Case2 were meant for validation purposes only. Good agreement was achieved with the previous research with a maximum error of 2%. The results showed that the circular design of the two-ring burner was the best choice which gave the optimum electric power from the system of about 121.1 kW. It was noted that the circular design of the two-ring burner achieved the highest thermal efficiency, which amounted to 0.523%.